Southeast Asia : - Glover, Ian (RoutledgeFalmer, 2004)
This comprehensive and absorbing book traces the cultural history of Southeast Asia from prehistoric (especially Neolithic, Bronze-Iron age) times through to the major Hindu and Buddhist civilizations, to around AD 1300. Southeast Asia has recently attracted archaeological attention as the locus for the first recorded sea crossings; as the region of origin for the Austronesian population dispersal across the Pacific from Neolithic times; as an arena for the development of archaeologically rich Neolithic, and metal using communities, especially in Thailand and Vietnam, and as the backdrop for several unique and strikingly monumental Indic civilizations, such as the Khmer civilization centered around Angkor. Invaluable to anyone interested in the full history of the region.